Analisis Historis Pondok Pesantren Anwaar-Ul-Uloom Bontocani Kab. Bone Provinsi Sulawesi Selatan - Agus Agus (Peneliti.net, 2020)
The purpose of this study is to analyze the history of estabishing in pesantren Anwar-Ul-Uloom Bontocani province of South Sulawesi Regency. Focus in the problem was on the performance of the pesantren and leadeship Anwar-Ul-Uloom Bontocani province of South Sulawesi Regency. To address the issu posed. Date collection is carried outantle ground using observation techniques, interview and dokementation. The source of the date was pesantren, which included the founder of pesantren, leader of boarding schools and the local goverment. Data collected is then prepared using qualitative descriptive analysis with date reduction, date presentation and verification of date or deducation with drawel . As for the aproach used by historical aproach and the sosilogical aproach. Reseach shows that: 1) The reality of pesantren was initated by negotiation on family and approval of the local goverment. 2) Pesantren opesionalizing was led by one the tabligh members who was a close friend of the family of the founder of boarding school Anwar-Ul-Uloom Bontocani province of South Sulawesi Regency.